Electrophotographic member, process cartridge, and electrophotographic image forming apparatus
Patent Information
- Application Number
- JP2023121972
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2025-02-06
AI Technical Summary
【0007】 本開示の少なくとも一の態様によれば、長期に亘って良好な電子写真画像を形成し得る電子写真部材が提供される。また、本開示の少なくとも一の態様によれば、高品位な電子写真画像を安定して形成し得るプロセスカートリッジが提供される。さらに、本開示の少なくとも一の態様によれば、高品位な電子写真画像を安定して形成し得る電子写真画像形成装置が提供される。
Smart Images

Figure 2025018355000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an electrophotographic member used in an electrophotographic image forming apparatus such as a copying machine or a printer, a process cartridge, and an electrophotographic image forming apparatus. [Background technology]
[0002] In electrophotographic image forming devices, the tandem method is widely used, in which a toner image is formed on a photoconductor, and the toner images of each color (Y (yellow), M (magenta), C (cyan), and K (black)) are superimposed on an intermediate transfer belt, and then all of the toner images are transferred onto paper at once to obtain a full-color image. In electrophotographic devices that require high-speed printing and maintenance-free operation, photoconductors and intermediate transfer belts are required to have even higher durability. To achieve high durability, it is necessary to make the photoconductors and intermediate transfer belts less prone to wear. Attempts have been made to ensure high durability by coating the surface layer of electrophotographic members with a resin containing dispersed inorganic fillers to make them less prone to wear. In this configuration, the resin in the surface layer has insulating properties, so discharge occurs in the charging section, primary transfer section, and secondary transfer section, often causing image problems. For this reason, conductive fillers containing tin oxide are used as inorganic fillers.
[0003] In Patent Document 1, a conductive filler, such as antimony-doped tin oxide or phosphorus-doped tin oxide, is added to an acrylic resin as the surface layer of an organic photoreceptor, while in Patent Document 2, a metal oxide fine particle is added to an acrylic resin as the surface layer of an intermediate transfer belt. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2016-126163 A [Patent Document 2] JP 2017-187558 A Summary of the Invention [Problem to be solved by the invention]
[0005] At least one aspect of the present disclosure is directed to providing an electrophotographic member that contributes to the stable formation of high-quality electrophotographic images. Also, at least one aspect of the present disclosure is directed to providing a process cartridge that can stably form high-quality electrophotographic images. Furthermore, at least one aspect of the present disclosure is directed to providing an electrophotographic image forming apparatus capable of stably forming high-quality electrophotographic images. [Means for solving the problem]
[0006] According to one aspect of the present invention, 1. An electrophotographic member having at least a base layer and a surface layer on the base layer, the surface layer contains a binder resin, particles containing tin oxide, and at least one copolymer selected from the group consisting of a polyoxyethylene-polycaprolactone copolymer and a polyoxyethylene-polyvalerolactone copolymer, The binder resin contains a (meth)acrylic resin, The copolymer contains at least one functional group selected from the group consisting of a carboxy group and a phosphate group; An electrophotographic member is provided in which the content of the particles in the surface layer is 2.0 to 10.0% by volume. Effect of the Invention
[0007] According to at least one aspect of the present disclosure, an electrophotographic member capable of forming good electrophotographic images over a long period of time is provided. According to at least one aspect of the present disclosure, a process cartridge capable of stably forming high-quality electrophotographic images is provided. Furthermore, according to at least one aspect of the present disclosure, an electrophotographic image forming apparatus capable of stably forming high-quality electrophotographic images is provided. [Brief description of the drawings]
[0008] [Figure 1]Electrophotographic image forming apparatus [Diagram 2] Cross-sectional structure example of intermediate transfer belt [Diagram 3] Example of cross-sectional structure of photosensitive drum [Figure 4] Example of cross-sectional structure of process cartridge [Diagram 5] SEM image of the surface layer (a) and its binary image (b) DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] In this specification, the description of "XX or more and YY or less" or "XX to YY" expressing a numerical range means a numerical range including the lower and upper limits, which are the endpoints, unless otherwise specified. In addition, when a numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined. In addition, in this disclosure, for example, a description such as "at least one selected from the group consisting of XX, YY, and ZZ" means any of XX, YY, ZZ, a combination of XX and YY, a combination of XX and ZZ, a combination of YY and ZZ, or a combination of XX, YY, and ZZ. Additionally, the environment in which the measurements were taken was 23°C and 50% RH unless otherwise specified. In this disclosure, "Ω / □" is a unit of surface resistivity defined in Japanese Industrial Standards (JIS) K 6911:2006, and means "Ω / square."
[0010] According to the study by the present inventors, when a large amount of conductive filler is added to increase the conductivity of the surface layer in the photoreceptor according to Patent Document 1, the light transmittance of the surface layer is decreased, making it difficult to form a high-quality latent image. On the other hand, when the content of the conductive filler is reduced to increase the light transmittance of the surface layer, the conductivity of the surface layer is decreased. Also, in the intermediate transfer member according to Patent Document 2, when the content of the conductive filler is increased to increase the conductivity of the surface layer, the hardness of the surface layer increases, which may cause scratches on other members in contact with the intermediate transfer member, such as the surface of an electrophotographic photosensitive member, or cause wear of a cleaning member for cleaning the surface of the intermediate transfer belt. In view of the above problems, the present inventors have come to the realization that it is necessary to develop a conductive resin film that has high conductivity while suppressing the content of conductive particles. Based on this realization, further investigations have been carried out, and as a result, it has been found that a cured product of a coating film of a paint containing particles containing tin oxide as conductive particles (hereinafter also referred to as "tin oxide particles"), at least one copolymer selected from the group consisting of polyoxyethylene-polycaprolactone copolymer and polyoxyethylene-polyvalerolactone copolymer, and a raw material for a (meth)acrylic resin can exhibit high conductivity while suppressing the content of conductive particles. The reason why the above cured product exhibits high conductivity even though it contains a small amount of conductive tin oxide particles is believed to be because at least one copolymer selected from the group consisting of polyoxyethylene-polycaprolactone copolymer and polyoxyethylene-polyvalerolactone copolymer can cause the tin oxide particles to aggregate appropriately in the coating film, and as a result, a conductive path is efficiently formed by the tin oxide particles in the cured product.
[0011] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the drawings. However, the dimensions, materials, shapes, relative positions, etc. of the components described in the following embodiments should be appropriately changed depending on the configuration of the device to which the present invention is applied and various conditions, and will not be included within the scope of the present invention. It is not intended to limit the scope of the present invention to those only.
[0012] At least one aspect of the present disclosure is 1. An electrophotographic member having at least a base layer and a surface layer on the base layer, the surface layer contains a binder resin, particles containing tin oxide, and at least one copolymer selected from the group consisting of a polyoxyethylene-polycaprolactone copolymer and a polyoxyethylene-polyvalerolactone copolymer, The binder resin contains a (meth)acrylic resin, The copolymer contains at least one functional group selected from the group consisting of a carboxy group and a phosphate group; The content of the particles in the surface layer is 2.0 to 10.0% by volume.
[0013] [Electrophotographic materials] The electrophotographic member of the present disclosure has at least a base layer and a surface layer on the base layer. The material of the base layer is not particularly limited, and well-known materials can be used depending on the application of the electrophotographic member, as will be described in detail later. The surface layer contains a binder resin. The binder resin includes a (meth)acrylic resin. The (meth)acrylic resin is a general term for methacrylic resin and acrylic resin. The (meth)acrylic resin refers to a copolymer of an acrylic acid ester or a methacrylic acid ester. The acrylic acid ester and the methacrylic acid ester are not particularly limited, and include those containing functional groups other than ester bonds, such as urethane acrylate and urethane methacrylate. The inclusion of a (meth)acrylic resin improves the adhesion and mechanical strength between the surface layer and the base layer. The content of the binder resin in the surface layer is not particularly limited, but in order to impart excellent strength to the surface layer and to impart excellent toner releasability to the outer surface of the surface layer, it is preferable that the content be 20 to 90% by mass with respect to the mass of the total solid content of the surface layer.
[0014] The surface layer can be formed as a cured film by polymerizing a composition containing a monomer having a polymerizable functional group (polymerizable monomer). The polymerization reaction is not particularly limited, and examples thereof include a thermal polymerization reaction, a photopolymerization reaction, and a radiation polymerization reaction. The polymerizable functional group of the monomer having a polymerizable functional group is not particularly limited as long as it can form a (meth)acrylic resin, and examples thereof include a methacryl group, an acrylic group, and an epoxy group.
[0015] Examples of the polymerizable monomer for forming the (meth)acrylic resin include the following (i) acrylate, (ii) methacrylate, (iii) urethane acrylate, and (iv) urethane methacrylate. As the polymerizable monomer, those commercially available as paints can also be used. (i) At least one acrylate selected from the group consisting of pentaerythritol triacrylate, pentaerythritol tetraacrylate, ditrimethylolpropane tetraacrylate, dipentaerythritol hexaacrylate, alkyl acrylate, benzyl acrylate, phenyl acrylate, ethylene glycol diacrylate, and bisphenol A diacrylate. (ii) At least one methacrylate selected from the group consisting of pentaerythritol trimethacrylate, pentaerythritol tetramethacrylate, ditrimethylolpropane tetramethacrylate, dipentaerythritol hexamethacrylate, alkyl methacrylate, benzyl methacrylate, phenyl methacrylate, ethylene glycol dimethacrylate, and bisphenol A dimethacrylate. (iii) At least one acrylate selected from the group consisting of polyether-based urethane acrylates and polyester-based urethane acrylates. (iv) Polyether-based urethane methacrylate, polyester-based urethane methacrylate At least one methacrylate selected from the group consisting of:
[0016] Considering that the surface layer will rub against other members, it is preferable that the surface layer has a high hardness. For this reason, it is preferable to use a crosslinkable monomer having two or more functionalities for the (meth)acrylic resin. This makes it possible to make the surface layer have a higher hardness. That is, among the acrylates of (i), at least one selected from the group consisting of pentaerythritol triacrylate, pentaerythritol tetraacrylate, ditrimethylolpropane tetraacrylate, and dipentaerythritol hexaacrylate is more preferable, and at least one selected from the group consisting of pentaerythritol triacrylate and pentaerythritol tetraacrylate is even more preferable. Among the methacrylates of (ii), at least one selected from the group consisting of pentaerythritol trimethacrylate, pentaerythritol tetramethacrylate, ditrimethylolpropane tetramethacrylate, and dipentaerythritol hexamethacrylate is more preferable, and at least one selected from the group consisting of pentaerythritol trimethacrylate and pentaerythritol tetramethacrylate is even more preferable. Furthermore, among the acrylates of (iii), at least one selected from the group consisting of difunctional or higher polyether-based urethane acrylates is more preferable, at least one selected from the group consisting of tetrafunctional or higher polyether-based urethane acrylates is even more preferable, and at least one selected from the group consisting of hexafunctional or higher polyether-based urethane acrylates is even more preferable. As such urethane acrylates, for example, U-6LPA (trade name, manufactured by Shin-Nakamura Chemical Co., Ltd.) can be mentioned. In addition, among the methacrylates of (iv), at least one selected from the group consisting of difunctional or higher polyether-based urethane methacrylates is more preferable, at least one selected from the group consisting of tetrafunctional or higher polyether-based urethane methacrylates is even more preferable, and at least one selected from the group consisting of hexafunctional or higher polyether-based urethane methacrylates is even more preferable.
[0017] In order to form a (meth)acrylic resin from such a polymerizable monomer, a photopolymerization initiator may be added and polymerization may be carried out by electron beam or ultraviolet light. Examples of the photopolymerization initiator include radical-generating photopolymerization initiators such as benzophenone, thioxanthone, benzyl dimethyl ketal, α-hydroxyketone, α-hydroxyalkylphenone, α-aminoketone, α-aminoalkylphenone, monoacylphosphine oxide, bisacylphosphine oxide, hydroxybenzophenone, aminobenzophenone, titanocene, oxime ester, and oxyphenylacetic acid ester.
[0018] <Particles containing tin oxide> The surface layer contains particles containing tin oxide. The tin oxide particles are not particularly limited, but for example, antimony-doped tin oxide particles, phosphorus-doped tin oxide particles, oxygen-deficient tin oxide particles, etc. can be used. These are preferred because they have low electrical resistance and are easily available. Among them, at least one selected from the group consisting of antimony-doped tin oxide particles and phosphorus-doped tin oxide particles is more preferred, and antimony-doped tin oxide particles or phosphorus-doped tin oxide particles are even more preferred.
[0019] The content ratio of tin oxide particles in the surface layer is 2.0 to 10.0% by volume. It is preferably 2.5 to 8.0% by volume, and more preferably 3.0 to 6.0% by volume. Within the above range, the surface resistivity and volume resistivity of the surface layer become favorable, and high-quality electrophotographic images can be formed. By making the content ratio 2.0% by volume or more, the surface layer has high conductivity. Furthermore, by making the content 10.0% by volume or less, it is possible to prevent the surface layer from becoming too hard.
[0020] <Polyoxyethylene-polycaprolactone copolymer and polyoxyethylene-polyvalerolactone copolymer> By forming a surface layer using a cured product of a coating film of a coating material for forming a surface layer, which contains at least one copolymer (hereinafter, sometimes simply referred to as "copolymer") selected from the group consisting of polyoxyethylene-polycaprolactone copolymer and polyoxyethylene-polyvalerolactone copolymer, together with conductive tin oxide particles and raw materials for (meth)acrylic resin (monomer, oligomer, etc.), the particles containing tin oxide in the surface layer can be brought into a desired aggregated state. As a result, high conductivity can be imparted to the surface layer. To obtain the copolymer, for example, ε-caprolactone can be subjected to ring-opening polymerization in the presence of polyoxyethylene having an OH group terminal, such as alcohol ethoxylate. The copolymer also contains at least one functional group selected from the group consisting of a carboxy group and a phosphate group. When the copolymer contains such a functional group, it becomes easier to adsorb to the surface of the tin oxide particles, and the affinity between the particles containing tin oxide and the copolymer is improved. In order to include such a functional group in the copolymer, for example, when the precursor of the copolymer contains a hydroxyl group, the hydroxyl group can be converted into a carboxyl group or a phosphate group by oxidation reaction. The content of the copolymer in the surface layer is not particularly limited, but is preferably 0.02 to 1.00% by mass.
[0021] The number average molecular weight of the copolymer is not particularly limited, but is preferably from 500 to 2500, more preferably from 600 to 2000, and further preferably from 800 to 1500. When it is within the above range, the particles containing tin oxide can be easily dispersed in a desired state.
[0022] The content of polyoxyethylene units in the copolymer is not particularly limited, but is preferably 20 to 55% by mass, more preferably 22 to 49% by mass, and even more preferably 29 to 44% by mass. By being in the above range, compatibility with the binder resin is good and the copolymer is easily adsorbed to particles containing tin oxide.
[0023] The surface layer may contain additives such as antioxidants, ultraviolet absorbers, plasticizers, leveling agents, slipping agents, and abrasion resistance improvers. Specific examples include hindered phenol compounds, hindered amine compounds, sulfur compounds, phosphorus compounds, benzophenone compounds, siloxane-modified resins, silicone oils, fluororesin particles, polystyrene resin particles, polyethylene resin particles, silica particles, alumina particles, and boron nitride particles. In addition, the surface layer may contain, for example, an organic compound having charge transport properties and a conductive filler other than particles containing tin oxide. The conductive filler is not particularly limited as long as it has conductivity, and examples thereof include metal oxides such as zinc oxide and indium oxide, carbon black, and metals.
[0024] The arithmetic mean thickness of the surface layer is not particularly limited, but is preferably, for example, 0.5 to 10 μm, and more preferably 2 to 10 μm. By being in the above range, the surface layer is easily maintained even after printing hundreds of thousands of sheets, and cracks and warping due to sliding are reduced. Furthermore, when the surface layer is formed using a paint, the arithmetic mean film thickness of the surface layer can be adjusted by the solids concentration of the paint or the amount of paint applied during coating.
[0025] [Electrophotographic photoreceptor] The electrophotographic member of the present disclosure can be used as an electrophotographic photoreceptor. That is, the electrophotographic member may be an electrophotographic photoreceptor. In this embodiment, an electrophotographic photoreceptor having components of a conductive support / conductive layer / undercoat layer / photosensitive layer / protective layer in this order will be described. In this case, the protective layer corresponds to the surface layer of the electrophotographic member, and layers other than the protective layer, such as the conductive layer, undercoat layer, and photosensitive layer, correspond to the base layer of the electrophotographic member. However, the present disclosure is not limited thereto. For example, the electrophotographic photoreceptor may not have a protective layer.
[0026] The electrophotographic photoreceptor of the present disclosure preferably includes a photosensitive layer. The photosensitive layer may include a single-layer type photosensitive layer or a multi-layer type photosensitive layer, as described below. When the electrophotographic photoreceptor includes a single-layer type photosensitive layer, the electrophotographic photoreceptor preferably has a single-layer type photosensitive layer and a protective layer that covers and protects the single-layer type photosensitive layer. When the electrophotographic photoreceptor includes a multi-layer type photosensitive layer, the electrophotographic photoreceptor preferably has a multi-layer type photosensitive layer and a protective layer that covers and protects the multi-layer type photosensitive layer. In these cases, the protective layer corresponds to the surface layer of the electrophotographic member.
[0027] The electrophotographic photoreceptor of the present disclosure may have a conductive support, and a charge generating layer and a charge transport layer in this order on the outer side of the conductive support. At least one layer selected from the group consisting of a conductive layer and an undercoat layer may be provided between the conductive support and the charge generating layer. A protective layer may be provided on the charge transport layer.
[0028] The method for producing the electrophotographic photoreceptor of the present disclosure includes a method in which a coating liquid for each layer described later is prepared, coated in the desired layer order, and cured by heating and drying, electron beam irradiation, etc. In this case, examples of the coating method for the coating liquid include dip coating, spray coating, inkjet coating, roll coating, die coating, blade coating, curtain coating, wire bar coating, ring coating, etc. Among these, dip coating is preferred from the viewpoints of efficiency and productivity.
[0029] Hereinafter, each component of an electrophotographic photoreceptor, such as a conductive support, a conductive layer, an undercoat layer, a photosensitive layer, and a protective layer, will be described. In the description of the photosensitive layer, (1) a multi-layer type photosensitive layer and (2) a single-layer type photosensitive layer will also be described.
[0030] <Conductive support> The electrophotographic photoreceptor may have a conductive support. The shape of the conductive support is not particularly limited, but may be, for example, a cylindrical shape, a belt shape, or a sheet shape. Of these, a cylindrical shape is preferable. The size of the conductive support is not particularly limited, but when it is cylindrical, it may have a diameter of 20 to 40 mm and an axial length of 200 to 500 mm. The thickness of the conductive support may be 0.1 to 2.0 mm. The surface of the conductive support may be subjected to electrochemical treatment such as anodization, blasting, cutting, or the like.
[0031] The material of the conductive support is not particularly limited, but is preferably a metal, a resin, a glass, etc. Examples of metals include aluminum, iron, nickel, copper, gold, stainless steel, and alloys thereof. Among them, an aluminum support using aluminum is preferable. When resin or glass is used, it is preferable to impart electrical conductivity to the resin or glass by a process such as mixing or coating with an electrically conductive material.
[0032] <Conductive layer> The electrophotographic photoreceptor may have a conductive layer on the conductive support. By having the conductive layer, scratches and irregularities on the surface of the conductive support can be concealed and light reflection on the surface of the conductive support can be prevented. It is possible to control the shot.
[0033] The conductive layer preferably contains a conductive filler and a resin. The material of the conductive filler is not particularly limited, but examples thereof include metal oxides, metals, and carbon black. Examples of metal oxides include zinc oxide, aluminum oxide, indium oxide, silicon oxide, zirconium oxide, tin oxide, titanium oxide, magnesium oxide, antimony oxide, and bismuth oxide. Examples of metals include aluminum, nickel, iron, nichrome, copper, zinc, and silver. Among these, it is preferable to use metal oxides as the conductive filler, and it is particularly preferable to use titanium oxide, tin oxide, or zinc oxide. When a metal oxide is used as the conductive filler, the surface of the metal oxide may be treated with a silane coupling agent or the like, or the metal oxide may be doped with an element such as phosphorus or aluminum or an oxide of these elements.
[0034] The conductive filler is preferably a conductive particle. The conductive particle may have a laminated structure having a core particle and a coating layer that covers the particle. Examples of the core particle include titanium oxide, barium sulfate, and zinc oxide. Examples of the coating layer include metal oxides such as tin oxide. When a metal oxide is used as the conductive filler, the volume average particle size of the metal oxide is preferably from 1 to 500 nm, and more preferably from 3 to 400 nm.
[0035] The resin used in the conductive layer is not particularly limited, but examples thereof include polyester resin, polycarbonate resin, polyvinyl acetal resin such as polyvinyl butyral resin, (meth)acrylic resin, silicone resin, epoxy resin, melamine resin, polyurethane resin, phenol resin, alkyd resin, etc. Among them, polyvinyl acetal resin is preferable.
[0036] The conductive layer may further contain silicone oil, resin particles, a masking agent such as titanium oxide, and the like. The arithmetic mean thickness of the conductive layer is preferably from 1 to 50 μm, and particularly preferably from 3 to 40 μm.
[0037] The conductive layer can be formed by preparing a coating liquid for the conductive layer containing the above-mentioned materials and solvent, forming a coating film, and curing the coating liquid by heating and drying, etc. Examples of the solvent used in the coating liquid for the conductive layer include alcohol-based solvents, sulfoxide-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents. Examples of the dispersion method for dispersing the conductive filler in the coating liquid for the conductive layer include a method using a paint shaker, a sand mill, a ball mill, and a liquid collision type high-speed disperser.
[0038] <Undercoat layer> The electrophotographic photoreceptor may have an undercoat layer on the conductive support or on the conductive layer. By having the undercoat layer, the adhesion function between layers can be improved and a charge injection blocking function can be imparted. The undercoat layer preferably contains a resin. Alternatively, the undercoat layer may be formed as a cured film by polymerizing a composition containing a monomer having a polymerizable functional group.
[0039] The resin used in the undercoat layer is not particularly limited, but examples thereof include polyester resins, polycarbonate resins, polyvinyl acetal resins such as polyvinyl butyral resins, (meth)acrylic resins, epoxy resins, melamine resins, polyurethane resins, phenolic resins, poly Examples of the resin include vinylphenol resin, alkyd resin, polyvinyl alcohol resin, polyethylene oxide resin, polypropylene oxide resin, polyamide resin, polyamic acid resin, polyimide resin, polyamideimide resin, and cellulose resin. Examples of the polymerizable functional group contained in the monomer having a polymerizable functional group include a carbon-carbon double bond group such as an isocyanate group, a blocked isocyanate group, a methylol group, an alkylated methylol group, an epoxy group, a metal alkoxide group, a hydroxy group, an amino group, a carboxy group, a thiol group, a carboxylic anhydride group, and a vinyl group.
[0040] For the purpose of improving electrical properties, the undercoat layer may further contain an electron transport material, a metal oxide, a metal, a conductive polymer, etc. Among these, it is preferable to use at least one selected from the group consisting of an electron transport material and a metal oxide. Examples of the electron transport substance include a quinone compound, an imide compound, a benzimidazole compound, a cyclopentadienylidene compound, a fluorenone compound, a xanthone compound, a benzophenone compound, a cyanovinyl compound, an aryl halide compound, a silole compound, and a boron-containing compound. An electron transport substance having a polymerizable functional group may be used as the electron transport substance, and the undercoat layer may be formed as a cured film by copolymerizing the electron transport substance with the monomer having the polymerizable functional group.
[0041] Metal oxides include indium tin oxide, tin oxide, indium oxide, titanium oxide, zinc oxide, aluminum oxide, silicon dioxide, etc. Metals include gold, silver, aluminum, etc. The undercoat layer may further contain additives such as silicone oil.
[0042] The arithmetic mean thickness of the undercoat layer is preferably from 0.1 to 50 μm, more preferably from 0.2 to 40 μm, and particularly preferably from 0.3 to 30 μm.
[0043] The undercoat layer can be formed by preparing a coating liquid for the undercoat layer containing the above-mentioned materials and solvent, forming a coating film from this, and curing the coating liquid by heating and drying, etc. Examples of the solvent used in the coating liquid include alcohol-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents.
[0044] <Photosensitive layer> The electrophotographic photoreceptor may have a photosensitive layer. The photosensitive layer is mainly classified into (1) a multi-layer type photosensitive layer and (2) a single-layer type photosensitive layer. Each type will be described in detail below.
[0045] (1) Laminated photosensitive layer The laminated photosensitive layer has a charge generating layer and a charge transport layer. The charge transport layer is preferably on the charge generating layer. When the charge transport layer is on the charge generating layer and the electrophotographic photoreceptor does not have a protective layer, the charge transport layer corresponds to the surface layer of the electrophotographic member, and the layers other than the charge transport layer correspond to the base layer of the electrophotographic member.
[0046] (1-1) Charge generation layer The charge generation layer contains a charge generation material. The charge generation layer preferably further contains a resin. The charge generation material is a material that generates charges and holes by exciting electrons in the HOMO orbital to the LUMO orbital in response to an external stimulus such as light. Examples of the charge generating material include pigments such as azo pigments, perylene pigments, polycyclic quinone pigments, indigo pigments, and phthalocyanine pigments. Among these, azo pigments and phthalocyanine pigments are preferred. Among phthalocyanine pigments, oxytitanium phthalocyanine pigments, chlorogallium phthalocyanine pigments, and hydroxygallium phthalocyanine pigments are more preferred, and hydroxygallium phthalocyanine pigments are even more preferred. The content of the charge generating material in the charge generating layer is preferably from 40 to 85% by mass, and more preferably from 60 to 80% by mass, based on the total mass of the charge generating layer.
[0047] Examples of resins used in the charge generating layer include polyester resins, polycarbonate resins, polyvinyl acetal resins such as polyvinyl butyral resins, (meth)acrylic resins, silicone resins, epoxy resins, melamine resins, polyurethane resins, phenol resins, polyvinyl alcohol resins, cellulose resins, polystyrene resins, polyvinyl acetate resins, polyvinyl chloride resins, etc. Among these, polyvinyl butyral resins are more preferred.
[0048] The charge generating layer may further contain additives such as an antioxidant and an ultraviolet absorbing agent, etc. Specific examples of such additives include hindered phenol compounds, hindered amine compounds, sulfur compounds, phosphorus compounds, and benzophenone compounds. The arithmetic mean thickness of the charge generating layer is preferably from 0.10 to 1.00 μm, and more preferably from 0.15 to 0.40 μm.
[0049] The charge generating layer can be formed by preparing a coating liquid for the charge generating layer containing the above-mentioned materials and solvent, forming a coating film of this, and curing the coating liquid by heating and drying, etc. Examples of the solvent used in the coating liquid include alcohol-based solvents, sulfoxide-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents.
[0050] (1-2) Charge transport layer The charge transport layer contains a charge transport material. The charge transport layer preferably further contains a resin. The charge transport material is also called a charge moving material, and is a material that has high mobility of electrons or holes and can receive electrons or holes generated in the charge generating layer. Examples of the charge transport material include polycyclic aromatic compounds, heterocyclic compounds, hydrazone compounds, styryl compounds, enamine compounds, benzidine compounds, triarylamine compounds, and resins having groups derived from these materials. Among these, triarylamine compounds and benzidine compounds are preferred. Examples of the benzidine compound include, but are not limited to, a compound represented by the following formula (B). Examples of the triarylamine compound include, but are not limited to, at least one selected from the group consisting of a compound represented by the following formula (C) and a compound represented by the following formula (D). [ka] [ka] [ka]
[0051] The content of the charge transport material in the charge transport layer is preferably from 25 to 70% by mass, and more preferably from 30 to 55% by mass, based on the total mass of the charge transport layer.
[0052] Examples of the resin used in the charge transport layer include polyester resin, polycarbonate resin, (meth)acrylic resin, and polystyrene resin. Among these, polycarbonate resin and polyester resin are preferable. As the polyester resin, polyarylate resin is particularly preferable. It is more preferable that the polycarbonate resin has a structural unit represented by the following formula (E) and a structural unit represented by the following formula (F). [ka] [ka]
[0053] When the charge transport layer is used as the surface layer, the binder resin that can be used for the surface layer described above can be used. The content ratio (mass ratio) of the charge transport material to the resin in the charge transport layer is preferably from 4:10 to 20:10, and more preferably from 5:10 to 12:10.
[0054] The charge transport layer may also contain additives such as antioxidants, ultraviolet absorbers, plasticizers, leveling agents, slipping agents, and abrasion resistance improvers. Specific examples of such additives include hindered phenol compounds, hindered amine compounds, sulfur compounds, phosphorus compounds, benzophenone compounds, siloxane-modified resins, silicone oils, fluororesin particles, polystyrene resin particles, polyethylene resin particles, silica particles, alumina particles, and boron nitride particles.
[0055] The arithmetic mean thickness of the charge transport layer is preferably from 5 to 50 μm, more preferably from 8 to 40 μm, and particularly preferably from 10 to 30 μm.
[0056] The charge transport layer can be formed by preparing a coating liquid for the charge transport layer containing the above-mentioned materials and solvent, forming a coating film, and curing the coating liquid by heating and drying, etc. Examples of the solvent used in the coating liquid include alcohol-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents. Among these solvents, at least one selected from the group consisting of ether-based solvents and aromatic hydrocarbon-based solvents is preferred.
[0057] (2) Single-layer photosensitive layer The single-layer type photosensitive layer contains a charge generating material and a charge transport material. The single-layer type photosensitive layer preferably further contains a resin. When the electrophotographic photoreceptor does not have a protective layer, the single-layer type photosensitive layer corresponds to the surface layer of the electrophotographic member, and the layers other than the single-layer type photosensitive layer correspond to the base layer of the electrophotographic member. The single-layer type photosensitive layer can be formed by preparing a coating liquid for the photosensitive layer containing a charge generating substance, a charge transporting substance, a solvent, etc., forming a coating film, and curing the coating liquid by heating and drying, etc. As the charge generating substance, charge transporting substance, resin, and solvent, the materials described in the above section "(1) Multi-layer type photosensitive layer" can be used.
[0058] <Protective layer> The electrophotographic photoreceptor may have a protective layer on the photosensitive layer. When the electrophotographic photoreceptor has a protective layer, the photosensitive layer is covered with the protective layer, so that the photosensitive layer can be protected from being scraped. As a result, the durability of the electrophotographic photoreceptor can be improved. The protective layer preferably contains a resin. The protective layer can also be a surface layer. When the protective layer is a surface layer, the binder resin that can be used for the above-mentioned surface layer can be used. When the protective layer is used as the surface layer, the protective layer contains the above-mentioned binder resin and particles containing tin oxide.
[0059] The protective layer may contain a conductive filler. By containing the conductive filler, the protective layer can be imparted with a charge transporting ability. The material of the conductive filler is not particularly limited, and may be, The particles containing tin oxide described in the above-mentioned surface layer section and the conductive filler described in the above-mentioned conductive layer section can be used. The protective layer may contain additives such as antioxidants, ultraviolet absorbers, plasticizers, leveling agents, and slipping agents, etc. Specific examples of such additives include hindered phenol compounds, hindered amine compounds, sulfur compounds, phosphorus compounds, benzophenone compounds, siloxane-modified resins, silicone oils, polystyrene resin particles, polyethylene resin particles, silica particles, alumina particles, and boron nitride particles.
[0060] The arithmetic mean thickness of the protective layer is preferably from 0.5 to 10 μm, more preferably from 1 to 7 μm, and may be from 2 to 10 μm. The protective layer can be formed by preparing a coating solution for the protective layer containing the above-mentioned materials and solvent, forming a coating film, and curing the coating solution by heating and drying, irradiating with an electron beam, etc. Examples of the solvent used in the coating solution include alcohol-based solvents, ketone-based solvents, ether-based solvents, sulfoxide-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents.
[0061] The surface resistivity of the surface layer of the electrophotographic photoreceptor when 100 V is applied is 3.0×10 9 ~1.0×10 12 Ω / □ is preferable, and 7.0×10 9 ~5.0×10 11 It is more preferable that the resistivity is Ω / □. When the resistivity is within the above range, the occurrence of discharge in the voltage application section is suppressed, and image defects due to deterioration of the photoreceptor surface layer caused by discharge are easily prevented. The surface resistivity can be adjusted, for example, by the amount of particles containing tin oxide. The method for measuring the surface resistivity will be described later.
[0062] [Process cartridge] The electrophotographic photoreceptor of the present disclosure can be used in a process cartridge. That is, the process cartridge integrally includes the electrophotographic photoreceptor of the present disclosure and at least one unit selected from the group consisting of a charging unit, a developing unit, a transfer unit, and a cleaning unit. In addition, the process cartridge is preferably configured to be detachably attached to the main body of an electrophotographic image forming apparatus.
[0063] [Electrophotographic image forming device] The electrophotographic member of the present disclosure can be used in an electrophotographic image forming apparatus. That is, the electrophotographic image forming apparatus includes the electrophotographic photoreceptor of the present disclosure. The electrophotographic image forming apparatus also includes a charging unit, an exposure unit, a developing unit, and a transfer unit, as described above. FIG. 4 shows an example of a schematic cross-sectional configuration of an electrophotographic image forming apparatus having a process cartridge equipped with an electrophotographic photosensitive member.
[0064] [Electrophotographic belt] The electrophotographic member of the present disclosure can be used as an electrophotographic belt, that is, the electrophotographic member can be an electrophotographic belt. In this embodiment, the electrophotographic belt has at least a base layer 21 and a surface layer 22 on the base layer 21, as illustrated in Fig. 2. In other words, the electrophotographic belt can be said to be a laminate. However, the electrophotographic belt may have layers other than these, and may add a primer layer between each layer to improve adhesion, a stress relaxation layer to suppress cracking of the surface layer 22, or an intermediate layer to suppress bleeding.
[0065] (base layer) The shape of the base layer 21 is not particularly limited, but may be, for example, a roll or belt shape, and is preferably an endless cylindrical shape. The material of the base layer 21 is not particularly limited, but examples thereof include the following: polyether ether ketone, polyethylene terephthalate, polybutylene naphthalate, polyester Resins such as ether, polyimide, polyamide, polyamideimide, polyacetal, polyphenylene sulfide, and polyvinylidene fluoride. Among these, polyimide is preferred because it can provide environmental stability.
[0066] The base layer 21 may contain a conductive compound such as metal powder, conductive oxide powder, conductive carbon, lithium salt, and ionic liquid to impart conductivity. In particular, the base layer preferably contains carbon black from the viewpoint of obtaining excellent conductivity and environmental stability. Combinations of other resins and conductive agents exemplified above may also be used. The base layer may be subjected to a surface treatment in order to further improve the adhesion with the surface layer. The method of the surface treatment is not particularly limited, but may be, for example, a corona treatment.
[0067] The thickness of the base layer 21 is preferably 10 to 500 μm. If it is less than 10 μm, the mechanical strength may decrease. If it is more than 500 μm, the rigidity may increase, making it difficult to use the base layer as an intermediate transfer member.
[0068] (Surface layer) The surface layer 22 corresponds to the surface layer of the electrophotographic member described above. The surface layer 22 contains the above-mentioned binder resin, tin oxide particles, and at least one copolymer selected from the group consisting of polyoxyethylene-polycaprolactone copolymers and polyoxyethylene-polyvalerolactone copolymers.
[0069] (Volume resistivity of electrophotographic belt) When the volume resistivity of the electrophotographic belt is high, the surface charge (residual charge) of the electrophotographic belt may not decay easily after the electrophotographic belt is transferred and charged by the secondary transfer member. In this case, the toner image on the photosensitive drum may be affected by the residual charge before the photosensitive drum and the electrophotographic belt come into contact during the next primary transfer, and part of the toner image may scatter when transferred onto the electrophotographic belt, resulting in a deterioration in image quality. In addition, unevenness may occur in the residual charge on the electrophotographic belt, which may cause uneven scattering and result in image unevenness. From this viewpoint, when the volume resistivity of the electrophotographic belt is ρv1, it is preferable that ρv1 satisfies the following formula (2), and more preferably satisfies the following formula (2-1). ρv1 can be adjusted by the amount and dispersion state of the particles containing tin oxide. The method for measuring ρv1 will be described later. 1.0×10 8 Ω cm≦ρv1≦1.0×10 12 Ω cm (2) 1.0×10 8 Ω cm≦ρv1≦7.0×10 11 Ω cm (2-1)
[0070] Furthermore, when the volume resistivity measured after removing the surface layer from the electrophotographic member is ρv2, it is preferable that ρv1 and ρv2 satisfy the following formula (1), and more preferably the following formula (1-1). ρv2 indicates the volume resistivity of the portion of the electrophotographic belt other than the surface layer. For example, when the electrophotographic belt is composed of a base layer and a surface layer on the base layer, it indicates the volume resistivity of the base layer. By satisfying the following formula (1), discharge at the voltage application portion can be prevented. ρv1 can be adjusted by the amount of conductive filler in the base layer and the amount of conductive filler such as particles containing tin oxide in the surface layer. The method for measuring ρv2 will be described later. 0.5≦log 10 (ρv1 / ρv2)≦3.5 (1) 1.0≦log 10 (ρv1 / ρv2)≦2.5 (1-1)
[0071] [Method of measuring arithmetic mean film thickness] The arithmetic average film thickness of each layer, for the surface layer, can be determined, for example, by using an interference film thickness meter (product name: F20; manufactured by Filmetrics) and fitting the interference waveform in the wavelength range of 500 to 900 nm based on reflectance spectroscopy using software provided with the device.
[0072] [Evaluation of the dispersion state in the surface layer of particles containing tin oxide] In the L function that indicates the relationship of the distribution of tin oxide particles observed from the surface of the surface layer, it is preferable that the value of the L function is always positive in the range of 300 nm to 1 μm in distance from the center of gravity coordinate of the particle.
[0073] The method for evaluating the dispersion state in the surface layer of tin oxide particles using the L function is as follows. The L function is explained below. Ripley's K function is defined as follows. K(d)=E / λ Here, E is the number of points within a circle of radius d centered on a randomly selected point, and λ is the density (average density) of points in the entire region. In other words, Ripley's K function, K(d), is the average number of other points contained within a circle of radius d centered on a randomly selected point, divided by the density (average density) of points in the entire area. When points are randomly scattered on a finite plane, they follow a Poisson distribution. Here, if points are randomly distributed according to a Poisson distribution, the expected number of other points present within a circle of radius d is calculated by multiplying the average density λ by the area of the circle πd. 2 This is the multiplied value and is expressed as follows: K(d) = πd 2
[0074] Here, the L function is obtained by standardizing Ripley's K function and making it a linear function. The L function L(d) is expressed as follows: L(d)=√(K(d) / π)-d Considering an index called the L function, when points are distributed randomly regardless of the radius d, L(d) = 0. Furthermore, L(d) takes a positive value when the spatial distribution is concentrated (clustered distribution), and takes a negative value when the distribution is regular (constant interval distribution). In other words, taking the random distribution as the base, if there are more other points within a certain radius d than in the random distribution, the value will be positive, and if there are fewer other points than in the random distribution, the value will be negative.
[0075] The distribution state of tin oxide particles can be evaluated by the fact that there are many adjacent tin oxide particles when the L function is positive at a small radius d. The dispersion diameter of tin oxide particles in the surface layer is usually distributed in the range of 300 nm to 1 μm. For this reason, in the present disclosure, the L function is evaluated in the range of distances from the center coordinates of the radius d to the center coordinates of one particle (group) of interest.
[0076] Here, for example, when the dispersion diameter of tin oxide particles in the surface layer is 300 nm, the L function being positive when the distance from the center of gravity coordinate is 300 nm to 1 μm means that the number of particles (groups) having center of gravity coordinates within a distance of 300 nm to 1 μm from the center of gravity coordinate of the particle (group) of interest is greater than in the case of random distribution. Hereinafter, the distance from the center of gravity coordinate may be referred to as the interparticle distance.
[0077] Therefore, the fact that the L function value L(d) is always positive in the interparticle distance range of 300 nm to 1 μm indicates that tin oxide particles are distributed in the form of clusters in the surface layer in the interparticle distance range of 300 nm to 1 μm.
[0078] The surface layer containing tin oxide particles may be a dried film of a coating material in which particles containing tin oxide are dispersed in a binder resin or its raw material, or a cured film of the coating material. In a surface layer formed using a paint in which tin oxide particles are dispersed, the distribution state of the tin oxide particles depends on the dispersion state of the tin oxide particles in the paint. Usually, tin oxide particles in paint are highly dispersed using a dispersant to prevent variations in the quality of the paint film. The distribution of the particles is considered to be random, i.e., L(d) = 0. In addition, the distribution of the tin oxide particles in the surface layer formed using a paint that has been left for a long period of time and in which the tin oxide particles have aggregated is considered to be aggregated at regular intervals, i.e., L(d) < 0.
[0079] In order to obtain the L function that indicates the state of existence of tin oxide particles in the surface layer, an evaluation sample is first prepared. A specimen having a length of 5 mm, a width of 5 mm, and a thickness equal to the entire thickness of the electrophotographic member is taken from an arbitrary position of the electrophotographic member. Next, the surface of the surface layer is observed with a scanning electron microscope (SEM) (product name: FE-SEM JSM-F100, manufactured by JEOL Ltd.) and a backscattered electron image of the surface is obtained (Figure 5(a)). The observation conditions are backscattered electron image mode at 3000x magnification, and the backscattered electron image acquisition conditions are accelerating voltage: 5.0 kV, working distance: 6 mm. A backscattered electron image provides a lot of compositional information, that is, the higher the atomic number of the element, the brighter it is, and since tin oxide particles contain tin atoms with a high atomic number, they are observed to be bright.
[0080] Next, the obtained image (42.7 μm × 32.0 μm) is binarized using image processing software so that the areas of the tin oxide particles are white and the areas of the (meth)acrylic resin other than the tin oxide particles are black (Figure 5 (b)). By binarizing the image by making the volume percentage, or area percentage, of particles containing tin oxide white starting from the brighter side and making the rest black, it is possible to obtain an image in which only the areas of the tin oxide particles are extracted as white. As image processing software, for example, "ImageJ" (distributed by the National Institutes of Health) can be used.
[0081] The specific conditions for binarization are as follows: first, the SEM image is loaded into image processing software and converted into a 256-level brightness image. Next, binarization is performed to separate only the tin oxide particle areas into white and the binder resin areas into black. The threshold value at this time is determined so that the occupied area ratio of the white areas after binarization (the ratio of the number of pixels occupied by the white areas to the total number of pixels in one SEM image) matches the content ratio of tin oxide particles. The content ratio of tin oxide particles in the surface layer can be calculated from the mass percentage of the binder resin, tin oxide particles, and other additives obtained by thermogravimetric analysis (TGA analysis) of the surface layer, and then calculated from the density of each.
[0082] From the obtained binarized image, the planar center of gravity coordinate values (X coordinate, Y coordinate) and number average particle diameter of the tin oxide particles are determined. Specifically, for example, the above-mentioned image processing software is used to determine the planar center of gravity coordinates of each particle by using the analyze function for the tin oxide particle portion (white portion) in the binarized image.
[0083] For the number-average particle size, first, the circle-equivalent diameter of each particle is calculated. The circle-equivalent diameter of each particle means the diameter of a circle having the same area as the area of the particle. Specifically, the number of pixels constituting each particle is calculated, and the actual particle area is calculated by multiplying this number of pixels by the area of one pixel.
[0084] In the SEM images used in the examples described later, the length of one side of one pixel corresponds to 0.15 μm, so the number of pixels constituting each particle is 0.15 × 0.15 μm. 2 Multiplied by. The diameter of a circle having this area is then calculated to obtain the equivalent circle diameter, and the sum of the equivalent circle diameters of each particle thus obtained is divided by the total number of particles to calculate the number average dispersion diameter.
[0085] Next, the Ripley's K function is calculated from the planar center of gravity coordinate values (X coordinate, Y coordinate) of the tin oxide particle using the following formula.
number
[0086] where i is the index of each particle in the image, λ is the average density of particles in the image, and n is the number of particles in the image. i is the ratio (area B / area A) of the area of circle i of radius d centered on the center of gravity of particle i to the area of circle i of radius d centered on the center of gravity of particle i that is included in the image. i is used to correct the underestimation caused by the absence of particles outside the image when particle i exists near the image boundary. d(i, j) is a function that takes the value of 1 when the coordinates of the center of gravity of particle j are within a circle of radius d centered on the coordinates of the center of gravity of particle i, and takes the value of 0 otherwise. In this disclosure, the radius d is a discrete function that takes a value for every pixel (0.033 μm) of the image.
[0087] Next, the value of the L function L(d) was calculated from Ripley's K function using the following formula when the interparticle distance d (radius d) was in the range of 300 nm to 1 μm.
number
[0088] The value of the L function is always positive when the interparticle distance is in the range of 300 nm to 1 μm, which means that the above value of L(d) is always positive when the interparticle distance d is in the range of 300 nm to 1 μm. In addition, in the range where the radius d is smaller than the minimum dispersed diameter of the tin oxide particles, other tin oxide particles cannot exist, so the value L(d) of the L function becomes large and negative.
[0089] In order to ensure that the value of the L function is always positive within the interparticle distance range of 300 nm to 1 μm, it is effective to incorporate a (meth)acrylic resin and a copolymer having a specific structure. In addition, in the interparticle distance range of 300 nm to 1 μm, the maximum value of the L function is preferably 0.3 or more, more preferably 0.3 to 5.0, and even more preferably 0.3 to 2.0. Also, for example, in the interparticle distance range of 300 nm to 1 μm, it is preferable that the value of the L function is always more than 0 and not more than 5.0, 0.3 to 5.0, or 0.3 to 2.0.
[0090] [Electrophotographic image forming device] An electrophotographic image forming apparatus 100 shown in FIG. 1 is a schematic cross-sectional view of an electrophotographic image forming apparatus equipped with an electrophotographic member according to one embodiment of the present disclosure.
[0091] The electrophotographic image forming apparatus 100 shown in FIG. 1 is equipped with an intermediate transfer belt (electrophotographic belt) 7, which is an intermediate transfer body. In addition, image forming units Py, Pm, Pc, and Pk of the respective colors of yellow (Y), magenta (M), cyan (C), and black (K) are arranged along the flat portion of the intermediate transfer belt 7 in the moving direction of the belt. In FIG. 1, 1Y, 1M, 1C, and 1K respectively indicate electrophotographic photosensitive members, and 2Y, 2M, 2C, and 2K respectively indicate charging rollers. In addition, 3Y, 3M, 3C, and 3K respectively indicate laser exposure devices, 4Y, 4M, 4C, and 4K respectively indicate developing devices, and 5Y, 5M, 5C, and 5K respectively indicate primary transfer rollers. Since the basic configuration of each image forming unit is the same, the details of the image forming units will not be described below. Regarding the yellow image forming unit Py, only the yellow image forming unit Py will be described.
[0092] The yellow image forming unit Py has a drum-shaped electrophotographic photosensitive member 1Y (hereinafter also referred to as a "photosensitive drum" or a "first image carrier") as an image carrier. The photosensitive drum 1Y is formed by laminating a charge generating layer, a charge transport layer, and a surface protective layer in this order on an aluminum cylinder as a base. A cross-sectional view of the photosensitive drum is shown in FIG. 3. Here, 31 is the aluminum cylinder, 32 is the charge generating layer, 33 is the charge transport layer, and 34 is the surface protective layer. Further, the yellow image forming unit Py includes a charging roller 2Y as a charging means. By applying a charging bias to the charging roller 2Y, the surface of the photosensitive drum 1Y is uniformly charged.
[0093] A laser exposure device 3Y is disposed above the photosensitive drum 1Y as an image exposure means. The laser exposure device 3Y scans and exposes the uniformly charged surface of the photosensitive drum 1Y in accordance with image information, forming an electrostatic latent image of a yellow color component on the surface of the photosensitive drum 1Y. The electrostatic latent image formed on the photosensitive drum 1Y is developed by the developing device 4Y as a developing means with toner as a developer. The developing device 4Y includes a developing roller 4Ya as a developer carrier and a regulating blade 4Yb as a developer amount regulating member, and contains yellow toner as a developer. The developing roller 4Ya to which the yellow toner is supplied is lightly pressed against the photosensitive drum 1Y in the developing section, and rotates in the forward direction with a speed difference from the photosensitive drum 1Y. The yellow toner conveyed to the developing section by the developing roller 4Ya adheres to the electrostatic latent image formed on the photosensitive drum 1Y by applying a developing bias to the developing roller 4Ya. As a result, a visible image (yellow toner image) is formed on the photosensitive drum 1Y.
[0094] The intermediate transfer belt 7 is stretched around a drive roller 71, a tension roller 72, and a driven roller 73, and is moved (rotationally driven) in the direction of the arrow in the figure by contacting the photosensitive drum 1Y. A cross-sectional view of the intermediate transfer belt is shown in Figure 2. Here, 21 is a base layer, and 22 is a surface protection layer. The yellow toner image formed on the photosensitive drum (first image carrier) that has reached the primary transfer portion Ty is primarily transferred onto the intermediate transfer belt 7 by a primary transfer body (primary transfer roller 5Y) that is arranged opposite the photosensitive drum 1Y via the intermediate transfer belt 7. Similarly, the above image forming operation is performed in each of the magenta (M), cyan (C) and black (K) units Pm, Pc and Pk as the intermediate transfer belt 7 moves, and toner images of four colors, yellow, magenta, cyan and black, are stacked on the intermediate transfer belt 7. The four color toner layers are transported as the intermediate transfer belt 7 moves, and are transferred collectively at the secondary transfer portion T' by a secondary transfer roller 8 as a secondary transfer means onto a transfer material S (hereinafter also referred to as a "second image carrier") transported at a predetermined timing. In such secondary transfer, a transfer voltage of several kV is usually applied to ensure a sufficient transfer rate.
[0095] The transfer material S is supplied to a conveying path from a cassette 12 in which the transfer material S is stored by a pickup roller 13. The transfer material S supplied to the conveying path is conveyed to a secondary transfer portion T' in synchronization with the four-color toner image transferred to the intermediate transfer belt 7 by a conveying roller pair 14 and a registration roller pair 15. The toner image transferred to the transfer material S is fixed by a fixing device 9 to become, for example, a full-color image. The fixing device 9 has a fixing roller 91 equipped with a heating means and a pressure roller 92, and fixes the unfixed toner image on the transfer material S by applying heat and pressure. Thereafter, the transfer material S is discharged outside the machine by a pair of conveying rollers 16, a pair of discharge rollers 17, etc.
[0096] As described above, the electrical transfer process of the toner image is repeated from the photoconductor to the intermediate transfer belt and from the intermediate transfer belt to the transfer material. Furthermore, by repeating recording on a large number of transfer materials, the electrical transfer process is further repeated. EXAMPLES
[0097] The present invention will be described in more detail below using examples and comparative examples. The present disclosure is not limited in any way by the following examples, as long as it does not exceed the gist of the disclosure. In the following description of the examples, "parts" are based on mass unless otherwise specified.
[0098] (Production Example of Copolymer β1) The following three compounds were mixed in a nitrogen atmosphere and reacted at 180°C for 8 hours with stirring to obtain a hydroxyl group-containing poly-ε-caprolactone-polyoxyethylene copolymer α1. Alcohol ethoxylates (Product name: Genapol C100; Clariant) 41 parts by weight ε-caprolactone (Tokyo Chemical Industry Co., Ltd.) 31 parts by weight Dibutyltin dilaurate (Tokyo Chemical Industry Co., Ltd.) 0.005 parts by mass The structural formula of "Genapol C100" is as follows. HO-(CH2CH2O)n-(CH2)m-CH3 (n=10, m=11 or 17)
[0099] The obtained hydroxyl group-containing poly-ε-caprolactone-polyoxyethylene copolymer α1 was mixed with phosphoric acid in the following ratio and reacted at 80°C for 6 hours with stirring. During the reaction, dehydration was carried out using molecular sieve 3A. The reaction yielded a copolymer, poly-ε-caprolactone-polyoxyethylene copolymer β1 containing phosphoric acid groups. ·α1 100 parts by mass Phosphoric acid (concentration 89% or more, manufactured by Tokyo Chemical Industry Co., Ltd.) 15 parts by weight
[0100] (Production Example of Copolymer β2) Copolymer β2 was obtained in the same manner as in Production Example for Copolymer β1, except that ε-caprolactone was changed to γ-valerolactone and the parts by mass of γ-valerolactone was changed to 18 parts by mass.
[0101] (Production Example of Copolymer β3) Copolymer α3 was obtained in the same manner as copolymer α1, except that Genapol C100 was changed to polyoxyethylene (4) lauryl ether (Kao Corporation, Emulgen 104P), ε-caprolactone was changed to Δ-valerolactone, and the mass parts of Δ-valerolactone were changed to 22 mass parts. The copolymer α3 was dissolved in ion-exchanged water having an electrical conductivity of 10 μS / cm or less to obtain a 20 mass% solution of the copolymer α3. 5 mass% of a platinum catalyst (E Add 1 part by mass of PMPC SP2010W (5% Pt on activated carbon, water wet, manufactured by Vonik) and place in a three-neck flask under nitrogen atmosphere. The mixture was then heated to 70°C in a water bath and held for 15 minutes, after which oxygen was passed through the system at a flow rate of 90 mL / min and the reaction continued for 18 hours. The oxygen was then switched to nitrogen and the catalyst was removed by filtration. The water solvent was evaporated to obtain poly-ε-caprolactone-polyoxyethylene copolymer β3 containing carboxyl groups.
[0102] (Production Example of Copolymer β4) Copolymer β4 was obtained in the same manner as for copolymer β1, except that the parts by mass of ε-caprolactone was changed to 77 parts by mass.
[0103] (Measurement of copolymer properties) The 1H-NMR of the copolymers β1 to β4 was measured using a 400 MHz NMR (JNM-ECA400 II) manufactured by JEOL, and the measurement results were analyzed to calculate the number average molecular weight and the proportion of PEG units in the molecule. The measurement method will be described in detail using copolymer β1 as an example. Copolymer β1 was dissolved in TMS-containing deuterated chloroform solvent (Tokyo Chemical Industry Co., Ltd.) and 1H-NMR was measured. Peak assignment was performed based on the peak derived from TMS, and the area ratio of the hydrogen atom corresponding to the terminal hydrocarbon, the hydrogen atom corresponding to the PEG unit, and the hydrogen atom corresponding to the polycaprolactone unit was calculated from 1H-NMR. Based on the area ratio, p, n, and m in the following formula (G) were calculated, and the number average molecular weight of copolymer β and the proportion of PEG units in one molecule were calculated. [ka]
[0104] Table 1 shows the raw material types, amounts added, and physical properties of the copolymers β1 to β4. [Table 1] In the table, POE unit refers to a polyoxyethylene unit.
[0105] (Production example of dispersion γ1) The following materials were placed in a glass standard bottle and dispersed for 4 hours using a paint shaker manufactured by Toyo Seiki Seisakusho, and then filtered through a nylon mesh with 60 μm openings to obtain dispersion liquid γ1. Antimony-doped tin oxide (Mitsubishi Materials Electronics) 40 parts by weight Poly-ε-caprolactone-polyoxyethylene copolymer β1 1.2 parts by mass 2-Propanol (Kishida Chemical) 30 parts by weight 30 parts by mass of 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether (product name: AE-3000, manufactured by AGC Corporation) φ0.8mm glass beads 30 parts by weight
[0106] (Production Examples of Dispersions γ2 to γ4 and Dispersions γS1 to γS3) Dispersions γ2 to 4 and dispersions γS1 to γS3 were obtained in the same manner as dispersion γ1, except that the types of conductive filler and additives were changed to those shown in Table 2. The following materials were used here. Phosphorus-doped tin oxide: Mitsubishi Materials Electronics Octadecyl phosphate: Manufactured by ALFA Chemistry 1-Decanol: Tokyo Chemical Industry Co., Ltd. Polyvinyl alcohol: Mn (number average molecular weight) = 20,000, manufactured by Sigma-Aldrich [Table 2]
[0107] (Paint A1 manufacturing example) The following materials were mixed with a magnetic stirrer to obtain paint A1. Mixture of pentaerythritol triacrylate and pentaerythritol tetraacrylate (product name: M306, manufactured by Toa Gosei) 70 parts by weight 1,1,2,2-Tetrafluoroethyl-2,2,2-trifluoroethyl ether (product name: AE-3000, manufactured by AGC Corp.) 50 parts by mass 2-Propanol (Kishida Chemical) 50 parts by weight ·Dispersion liquid γ1 40 parts by mass
[0108] (Production examples of paints A2 to A4 and AS1 to AS4) Paints A2 to A4 and AS1 to AS4 were obtained by preparing paints in the same manner as Paint A1, except that the types of monomer and dispersion, and the amount of dispersion added were changed to those shown in Table 3. Here, the following materials were used. Urethane acrylate: Product name: U-6LPA, manufactured by Shin-Nakamura Chemical Co., Ltd. [Table 3]
[0109] (Example A1) As a conductive support, an aluminum cylinder having a diameter of 30 mm, a length of 357.5 mm, and a wall thickness of 1 mm was prepared. Next, zinc oxide particles (specific surface area: 19 m) were used as conductive particles. 2 / g, powder resistance: 4.7×10 6 100 parts of toluene (resistance: Ω·cm) was stirred and mixed with 500 parts of toluene, to which 0.8 parts of a silane coupling agent (compound name: N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, product name: KBM602, manufactured by Shin-Etsu Chemical Co., Ltd.) was added and stirred for 6 hours. Thereafter, the toluene was distilled off under reduced pressure, and the mixture was dried by heating at 130°C for 6 hours to obtain surface-treated zinc oxide particles.
[0110] Next, 15 parts of polyvinyl butyral resin (product name: BM-1, manufactured by Sekisui Chemical Co., Ltd.) and 15 parts of blocked isocyanate (product name: Sumidur 3175, manufactured by Sumitomo Bayer Urethane Co., Ltd.) were dissolved in a mixed solution of 73.5 parts of methyl ethyl ketone and 73.5 parts of 1-butanol to obtain a solution. To the obtained solution, 80.64 parts of the above-mentioned surface-treated zinc oxide particles and 0.8 parts of a compound represented by the following formula (A) (manufactured by Tokyo Chemical Industry Co., Ltd.) were added, and the mixture was dispersed for 3 hours in an atmosphere of 23±3°C using a sand mill equipped with glass beads having a diameter of 0.8 mm. [ka]
[0111] After dispersion, 0.01 parts of silicone oil (product name: SH28PA, manufactured by Toray Dow Corning Silicones) and 5.6 parts of cross-linked polymethyl methacrylate (PMMA) particles (product name: TECHPOLYMER SSX-103, manufactured by Sekisui Chemical Co., Ltd., average primary particle size 3.1 μm) were added and stirred to prepare a coating solution for the undercoat layer. This undercoat layer coating liquid was dip-coated onto the conductive support to form a coating film, and the coating film was dried by heating at 145° C. for 40 minutes to form an undercoat layer having an arithmetic average thickness of 18 μm.
[0112] Next, 11 parts of hydroxygallium phthalocyanine crystals having strong peaks at Bragg angles (2θ±0.2°) of 7.4° and 28.2° in CuKα characteristic X-ray diffraction as a charge generating substance, 5 parts of polyvinyl butyral (product name: S-LEC BX-1, manufactured by Sekisui Chemical Co., Ltd.), and 130 parts of cyclohexanone were mixed, to which 500 parts of glass beads having a diameter of 1 mm were added, and the mixture was dispersed for 2 hours at 1800 rpm while being cooled with cooling water at 18°C. After the dispersion treatment, 300 parts of ethyl acetate and 160 parts of cyclohexanone were added to dilute the mixture to prepare a coating solution for the charge generation layer. The coating solution for the charge generation layer was dip-coated onto the undercoat layer, and the resulting coating was dried at 110° C. for 10 minutes to form a charge generation layer with an arithmetic mean thickness of 0.16 μm. The average particle size (median) of the hydroxygallium phthalocyanine crystals in the prepared coating liquid for the charge generating layer was measured using a centrifugal particle size measuring device (product name: CAPA700, manufactured by Horiba, Ltd.) based on the liquid phase sedimentation method, and was found to be 0.18 μm.
[0113] Next, 2 parts of the charge transport material represented by the following formula (B), 7 parts of the charge transport material represented by the following formula (C), 1 part of the charge transport material represented by the following formula (D), 10 parts of polycarbonate (trade name: Iupilon Z400, manufactured by Mitsubishi Gas Chemical Co., Ltd.), and 0.002 parts of polycarbonate A (viscosity average molecular weight Mv: 20000) having the structural unit represented by the following formula (E) and the structural unit represented by the following formula (F) were dissolved in a mixed solvent of 70 parts of monochlorobenzene and 30 parts of dimethoxymethane to prepare a coating solution for a charge transport layer. Here, in polycarbonate A, the ratio (molar ratio) of the structural unit represented by the following formula (E) to the structural unit represented by the following formula (F) was 95 / 5. [ka] [ka] [ka] [ka] [ka]
[0114] This coating liquid for the charge transport layer was dip-coated onto the charge generation layer, and the resulting coating was dried for 30 minutes at 100° C. to form a charge transport layer having an arithmetic mean thickness of 18 μm. In this example, the layer consisting of the conductive support, the undercoat layer, the charge generation layer, and the charge transport layer corresponds to the base layer. Next, the paint A1 was applied by dip coating onto the charge transport layer and heat-treated at 50°C for 5 minutes. After that, the coating film was irradiated with an electron beam for 1.6 seconds under conditions of an acceleration voltage of 70 kV and an absorbed dose of 50 kGy in a nitrogen atmosphere. Then, the coating film was heat-treated for 25 seconds under conditions of 130°C in a nitrogen atmosphere. The oxygen concentration from the irradiation of the electron beam to the heat treatment for 25 seconds was 20 ppm. Next, a surface layer with an arithmetic average thickness of 5 μm was formed by heat-treating the coating film for 12 minutes under conditions of 115°C in the atmosphere, to obtain a photoreceptor A1.
[0115] (Examples A2 to A6, Comparative Examples AS1 to AS4) Photoreceptors A2 to A6 and photoreceptors AS1 to AS4 were obtained in the same manner as in Example A1, except that a paint shown in Table 4 was used instead of paint A1 and the thickness shown in Table 4 was used.
[0116] (Evaluation of surface resistivity) A surface layer was formed on a 50 μm Lumirror film in the same manner as in Examples A1 to A6 and AS1 to AS4, and the surface resistivity was measured using a Hiresta-UX (manufactured by Mitsubishi Chemical Analytech) with a UR probe by applying a voltage of 100 V between the electrodes in accordance with JIS K 6911. The results are shown in Table 4.
[0117] (Evaluation of residual potential) For the photoreceptors according to Examples A1 to A6 and Comparative Examples AS1 to AS4 prepared above, the residual potential was evaluated under the following conditions. Using a photoconductor tester (product name: CYNTHIA59, manufactured by Gentec), the conditions of the charging device were set so that the surface of the electrophotographic photoconductor was -700V in an environment of 23°C / 50% RH. Monochromatic light with a wavelength of 780 nm was irradiated to the electroconductor, with the amount of light required to reduce the potential of -700V to -200V. Furthermore, a 20 (μJ / cm 2 The potential of the photoconductor when irradiated with a light amount of 10000 V was measured and taken as the residual potential (-V). The evaluation results are shown in Table 4.
[0118] (Durable image evaluation) As an electrophotographic apparatus, a copying machine (product name: iR ADVANCE C5560F, manufactured by Canon Inc.) was used. Characters with a font size of 5 points (1.764 mm square) were used to form an image, and it was visually evaluated whether the image was blurred or there were bleeding areas. For printing, after printing 10,000 sheets of A4-sized paper, power supply to the copying machine was stopped for 12 hours, and then the process of printing another 10,000 sheets was repeated. This process was repeated until 100,000 sheets were printed, and the 100,000th image was evaluated. The evaluation results are shown in Table 4.
[0119] <Evaluation of the dispersion state of tin oxide particles by the L function> Evaluation samples were prepared from the electrophotographic belt. Samples with a length of 5 mm, a width of 5 mm, and a thickness equal to the total thickness of the electrophotographic belt were collected from 12 locations on the electrophotographic belt. The collection locations were 3 locations in the width direction of the electrophotographic belt and 4 locations at 90° intervals in the circumferential direction. Among the 3 locations in the width direction, 1 location was set such that the center in the width direction coincided with the center in the width direction of the evaluation sample. For the other 2 locations, the inner side (midpoint side) 2 mm from both ends in the width direction coincided with one end in the width direction of the sample.
[0120] Subsequently, for each of the 12 evaluation samples, an arbitrary position on the surface corresponding to the outer surface of the surface layer (the surface opposite to the surface facing the base layer) was observed by scanning electron microscopy (SEM) (product name: FE-SEM S-4800, manufactured by Hitachi High-Technologies Corporation), and an SEM image with a size of 42.7 μm in length and 32.0 μm in width was obtained. The observation conditions were the backscattered electron image mode at 3000 times magnification, and the backscattered electron image acquisition conditions were an acceleration voltage of 5.0 kV and a working distance of 6 mm. In the obtained SEM image, the part of the tin oxide particles (group) was observed brightly.
[0121] Next, for the obtained SEM image, binarization processing was performed using image processing software (name: ImageJ; distributed by the National Institutes of Health, USA) so that the part of the tin oxide particles was white and the part of the binder resin was black. By making the volume percentage, that is, the area percentage, of the tin oxide particles white from the brighter side of the luminance and making the rest black for binarization, an image in which only the tin oxide particles were extracted as the white part was obtained.
[0122] The specific conditions for binarization were as follows: first, the SEM image was loaded into image processing software and converted into a 256-level grayscale brightness image. Next, binarization was performed to separate only the tin oxide particle areas into white and the binder resin areas into black. The threshold value at this time was determined so that the area ratio of the white areas after binarization (the ratio of the number of pixels occupied by the white areas to the total number of pixels in one SEM image) would match the content ratio of tin oxide particles.
[0123] From the obtained binarized image, the planar center coordinate values (X coordinate, Y coordinate) of the tin oxide particle (particles) and the number average particle diameter were obtained. Specifically, the planar center coordinates of each particle were obtained for the tin oxide particle portion (white portion) in the binarized image using the above-mentioned image processing software.
[0124] Regarding the number-average particle diameter, first, the circle-equivalent diameter of each particle was calculated. The circle-equivalent diameter of each particle refers to the diameter of a circle having the same area as the area of the particle. Specifically, the number of pixels constituting each particle (group) was calculated, and the actual particle area was calculated by multiplying this number of pixels by the area of one pixel. In the above SEM image, the length of one side of one pixel is equivalent to 0.15 μm, so the number of pixels constituting each particle was multiplied by 0.15 × 0.15 μm. 2 Multiplied by. The diameter of a circle having this area was calculated to obtain the equivalent circle diameter, and the sum of the equivalent circle diameters of each particle thus obtained was divided by the total number of particles to calculate the number-average dispersed diameter.
[0125] Next, the Ripley's K function was calculated from the planar center of gravity coordinate values (X coordinate, Y coordinate) of the tin oxide particle using the following formula.
number
[0126] where i is the index of each particle in the image, λ is the average density of particles in the image, and n is the number of particles in the image. iis the ratio (area B / area A) of the area of circle i of radius d centered on the center of gravity of particle i to the area of circle i of radius d centered on the center of gravity of particle i that is included in the image. i is used to correct the underestimation caused by the absence of particles outside the image when particle i exists near the image boundary. d (i, j) is a function that takes the value of 1 when the coordinates of the center of gravity of particle j are within a circle of radius d centered on the coordinates of the center of gravity of particle i, and takes the value of 0 otherwise. In this disclosure, the radius d is a discrete function that takes a value for every pixel (0.033 μm) of the image.
[0127] Next, the value of the L function L(d) was calculated from Ripley's K function using the following formula when the interparticle distance d (radius d) was in the range of 300 nm to 1 μm.
number
[0128] The value of the L function is always positive when the interparticle distance is in the range of 300 nm to 1 μm, which means that the above value of L(d) is always positive when the interparticle distance d is in the range of 300 nm to 1 μm. All of the L functions showing the distribution state of tin oxide particles (groups) obtained by analyzing SEM images created from each of the 12 evaluation samples using the above method had positive L function values when the interparticle distance was in the range of 300 nm to 1 μm. The results are shown in Table 1. In Table 1 showing the evaluation results described below, when "positive" is written in the item "Positive / Negative L Function (Interparticle Distance 300 nm to 1 μm)" showing the results of Evaluation 1, it indicates that all of the L functions obtained from the above analysis of the 12 evaluation samples were positive in the interparticle distance range of 300 nm to 1 μm. On the other hand, when "negative" is written in the same item, it indicates that at least one of the L functions obtained from the above analysis of the 12 evaluation samples was negative in the interparticle distance range of 300 nm to 1 μm. Also, when the L function was measured using an electrophotographic photosensitive member as the measurement object, an evaluation sample was prepared and measured in the same manner as in the case of the electrophotographic belt. [Table 4] In the table, the thickness indicates the arithmetic average film thickness (μm) of the surface layer, and the particle content indicates the content (volume %) of tin oxide particles relative to the surface layer.
[0129] As shown in Table 4, it was suggested that when the surface layer contains at least one copolymer selected from the group consisting of polyoxyethylene-polycaprolactone copolymer and polyoxyethylene-polyvalerolactone copolymer, the tin oxide particles in the surface layer moderately aggregate, reducing the surface resistivity and thereby reducing the residual potential. Even in the case of Comparative Example AS4, which does not contain a copolymer, the surface resistivity can be reduced by increasing the amount of conductive filler. However, it is presumed that the surface layer becomes hard and is hardly scraped off even when multiple sheets are printed, which makes it easier for blurred or bleeding images to occur.
[0130] (Paint B1 manufacturing example) The following materials were mixed with a magnetic stirrer to obtain paint B1. Mixture of pentaerythritol triacrylate and pentaerythritol tetraacrylate (product name: M306, manufactured by Toa Gosei) 70 parts by weight Methyl ethyl ketone (Kishida Chemical) 50 parts by weight 2-Propanol (Kishida Chemical) 50 parts by weight 1-Hydroxycyclohexyl phenyl ketone (Tokyo Chemical Industry Co., Ltd.) 5 parts by weight Photopolymerization initiator (Esacure ONE manufactured by IGM Resins) 3 parts by weight ·Dispersion liquid γ1 40 parts by mass
[0131] (Preparation of paint B2) Paints B2 to B4 and Paints BS1 to BS4 were obtained by preparing paints in the same manner as Paint B1, except that the types of monomer and dispersion, and the amount of dispersion added were changed to those shown in Table 5. Here, the following materials were used. Urethane acrylate: Product name: U-6LPA, manufactured by Shin-Nakamura Chemical Co., Ltd. [Table 5]
[0132] Example B1 Full-color electrophotographic image forming device (product name: imageRUNNER ADVANCE A corona treatment was performed on the outer peripheral surface of an intermediate transfer belt (single layer) having an endless shape made of polyimide with dispersed carbon black, which was attached to a printer (C5051; manufactured by Canon Inc.). Then, paint B1 was applied to the outer peripheral surface under conditions that would result in a dry film thickness of 5 μm, and dried at 70°C for 3 minutes. Then, a high-pressure mercury lamp was used to apply the paint, with a peak illuminance of 200 mW / cm at 365 nm. 2 , Accumulated light intensity 2J / cm 2 A surface layer was formed by irradiating ultraviolet rays under the above conditions, thereby obtaining the intermediate transfer belt 1. In this embodiment, the layer made of the polyimide seamless belt corresponds to the base layer.
[0133] (Examples B2 to B4, Comparative Examples BS1 to BS4) Intermediate transfer belts B2 to B4 and intermediate transfer belts BS1 to BS4 were obtained in the same manner as in Example B1, except that the type of paint was changed as shown in Table 6 and the thickness was set as shown in Table 6.
[0134] (Measurement of volume resistivity ρv1) Using a Hiresta-UX (manufactured by Mitsubishi Chemical Analytech), the volume resistivity ρv1 was measured by applying a voltage of 10 V between the electrodes with a UR probe in accordance with JIS K 6911. The results are shown in Table 6.
[0135] (Measurement of volume resistivity ρv2) The surface layer of the intermediate transfer belt was scraped off using an aluminum oxide wrapping film sheet manufactured by 3M, and then cleaned using a Toray MK manufactured by Toray. Using a Hiresta-UX (manufactured by Mitsubishi Chemical Analytec), a voltage of 10 V was applied between the electrodes with a UR probe in accordance with JIS K 6911 to measure the volume resistivity ρv2. Using the obtained values of ρv1 and ρv2, log 10 The value of (ρv1 / ρv2) was calculated.
[0136] (Evaluation of image defects) Using a copier (product name: iR ADVANCE C5560F, manufactured by Canon Inc.), 995 sheets of the following continuous printing image were printed, followed by 5 sheets of the following image defect confirmation image. This cycle was repeated 100 times to print 100,000 sheets. The environment was a temperature of 23°C and a relative humidity of 5%. [Images for continuous printing] -Paper used: GF-C081 A4 size (grammage 81.4g / m 2 , thickness 97μm, whiteness approx. 100%, manufactured by Canon Inc.) Printing image: All CMYK toners on the intermediate transfer belt are used, image ratio 20% [Image for checking image quality] -Paper used: GF-C081 A3 size (grammage 81.4g / m 2 , thickness 97μm, whiteness approx. 100%, manufactured by Canon Inc.) Print image: Halftone image using only K toner (density 50%), image ratio 100%
[0137] (Evaluation of cleaning properties) Using a copier (product name: iR ADVANCE C5560F, manufactured by Canon Inc.), 995 copies of the image for continuous printing shown below were printed, followed by 5 copies of the image defect confirmation image shown below. This cycle was repeated 100 times to print 100,000 copies. The environment was a temperature of 30°C and a relative humidity of 80%. [Image for continuous printing] -Paper used: GF-C081 A4 size (grammage 81.4g / m 2 , thickness 97μm, whiteness approx. 100%, manufactured by Canon Inc.) Printing image: All CMYK toners on the intermediate transfer belt are used, image ratio 5% [Image for checking image quality] -Paper used: GF-C081 A3 size (grammage 81.4g / m 2 , thickness 97μm, whiteness approx. 100%, manufactured by Canon Inc.) Print image: Image ratio 0% In the image for checking image defects, if an image defect occurred due to a cleaning defect of the transfer belt, it was marked as "occurred," and if there was no image defect, it was marked as "not occurred." The results are shown in Table 6. [Table 6] In the table, the thickness indicates the arithmetic average film thickness (μm) of the surface layer, and the particle content indicates the content (volume %) of tin oxide particles relative to the surface layer.
[0138] As shown in Table 6, it was found that the surface layer containing at least one copolymer selected from the group consisting of polyoxyethylene-polycaprolactone copolymer and polyoxyethylene-polyvalerolactone copolymer moderately aggregates tin oxide particles in the surface layer, lowering the volume resistivity, thereby providing a transfer belt with no image unevenness and good cleaning properties. On the other hand, in Comparative Examples BS1 to BS3, the tin oxide particles did not aggregate properly, and the volume resistivity was high, causing image unevenness. In Comparative Example BS4, the volume resistivity was lowered by adding a large amount of conductive filler, and the occurrence of image unevenness was prevented. However, the surface layer became hard, and when multiple sheets were printed, the cleaning member was scraped off, causing image defects due to poor cleaning.
[0139] The present disclosure relates to the following configurations. [Configuration 1] 1. An electrophotographic member having at least a base layer and a surface layer on the base layer, the surface layer contains a binder resin, particles containing tin oxide, and at least one copolymer selected from the group consisting of a polyoxyethylene-polycaprolactone copolymer and a polyoxyethylene-polyvalerolactone copolymer, The binder resin contains a (meth)acrylic resin, The copolymer contains at least one functional group selected from the group consisting of a carboxy group and a phosphate group; The electrophotographic member is characterized in that the content of the particles in the surface layer is 2.0 to 10.0% by volume. [Configuration 2] 2. The electrophotographic member of claim 1, wherein the particles comprise at least one selected from the group consisting of antimony-doped tin oxide and phosphorus-doped tin oxide. [Configuration 3] 3. The electrophotographic member of embodiment 1 or 2, wherein the electrophotographic member is an electrophotographic belt. [Configuration 4] The volume resistivity of the electrophotographic member is ρv1, and the surface layer is removed from the electrophotographic member. 4. The electrophotographic member according to configuration 3, wherein ρv1 and ρv2 satisfy the following formulae (1) and (2), where ρv2 is the volume resistivity measured by the above formula. 0.5≦log 10 (ρv1 / ρv2)≦3.5 (1) 1.0×10 8 Ω cm≦ρv1≦1.0×10 12 Ω cm (2) [Configuration 5] 3. The electrophotographic member according to embodiment 1 or 2, wherein the electrophotographic member is an electrophotographic photoreceptor. [Configuration 6] The surface resistivity of the surface layer when 100 V is applied is 3.0×10 9 ~1.0×10 11 6. The electrophotographic member of embodiment 5, wherein the resistivity is Ω / □. [Configuration 7] 7. The electrophotographic member according to any one of configurations 1 to 6, wherein the surface layer has an arithmetic mean thickness of 2 to 10 μm. [Configuration 8] 8. The electrophotographic member according to any one of configurations 1 to 7, wherein the number average molecular weight of the copolymer is from 600 to 2000, and the content of polyoxyethylene units in the copolymer is from 29 to 44% by mass. [Configuration 9] 9. The electrophotographic member according to any one of configurations 1 to 8, wherein an L function showing a distribution relationship of the particles containing tin oxide observed from the surface of the surface layer has a value that is always positive within a distance range of 300 nm to 1 μm from the center of gravity coordinate of the particle. [Configuration 10] 10. A process cartridge configured to be detachably mountable to a main body of an electrophotographic image forming apparatus, the process cartridge comprising the electrophotographic member according to any one of Configurations 1 to 9. [Configuration 11] An electrophotographic image forming apparatus comprising the electrophotographic member according to any one of Configurations 1 to 9. [Explanation of symbols]
[0140] Py: yellow image forming unit, Pm: magenta image forming unit, Pc: cyan image forming unit, Pk: black image forming unit, 1Y: yellow photosensitive drum, 1M: magenta photosensitive drum, 1C: cyan photosensitive drum, 1K: black photosensitive drum, 4Y: yellow developing device, 4M: magenta developing device, 4C: cyan developing device, 4K: black developing device, 5Y, 5M, 5C, 5K: primary transfer rollers, Ty, Tm, Tc, Tk: primary transfer unit, 73: secondary transfer inner roller, 100: image formation device, 2Y, 2M, 2C, 2K: charger, 3Y, 3M, 3C, 3K: laser scanner, 11: transfer belt cleaning unit, 12: paper feed cassette, 15: registration roller pair, 7: intermediate transfer belt, 8: secondary transfer outer roller, 9: fixing unit, 91: fixing film, 92: pressure roller, S: transfer material, 21: base layer of intermediate transfer belt, 22: surface layer of intermediate transfer belt, 31: conductive base layer of photoconductor, 32: charge generation layer of photoconductor, 33: charge transport layer of photoconductor, 34: surface layer of photoconductor
Claims
1. 1. An electrophotographic member having at least a base layer and a surface layer on the base layer, the surface layer contains a binder resin, particles containing tin oxide, and at least one copolymer selected from the group consisting of a polyoxyethylene-polycaprolactone copolymer and a polyoxyethylene-polyvalerolactone copolymer; The binder resin contains a (meth)acrylic resin, The copolymer contains at least one functional group selected from the group consisting of a carboxy group and a phosphate group; The content of said particles in said surface layer is 2.0 to 10.0% by volume.
2. 2. The electrophotographic member of claim 1 wherein said particles comprise at least one selected from the group consisting of antimony doped tin oxide and phosphorus doped tin oxide.
3. 2. The electrophotographic member of claim 1 wherein said electrophotographic member is an electrophotographic belt.
4. 4. The electrophotographic member according to claim 3, wherein ρv1 is a volume resistivity of the electrophotographic member, and ρv2 is a volume resistivity measured after removing a surface layer from the electrophotographic member, and ρv1 and ρv2 satisfy the following formulas (1) and (2): 0.5≦log 10 (ρ1 / ρ2)≦3.5 (1) 1.0×10 8 Ω・cm≦ρv1≦1.0×10 12 Ohm・cm (2)
5. 2. The electrophotographic member of claim 1, wherein said electrophotographic member is an electrophotographic photoreceptor.
6. The surface resistivity of the surface layer when 100 V is applied is 3.0×10 9 ~1.0 x 10 11 6. The electrophotographic member of claim 5, wherein the resistivity is Ω / □.
7. 2. The electrophotographic member of claim 1, wherein the surface layer has an arithmetic mean thickness of 2 to 10 μm.
8. 2. The electrophotographic member according to claim 1, wherein the number average molecular weight of said copolymer is from 600 to 2000, and the content of polyoxyethylene units in said copolymer is from 29 to 44% by weight.
9. 2. The electrophotographic member according to claim 1, wherein an L function showing a distribution relationship of the particles containing tin oxide observed from the surface of the surface layer has a value that is always positive when the distance from the center of gravity coordinate of the particle is in a range of 300 nm to 1 μm.
10. 10. A process cartridge configured to be detachably mountable to a main body of an electrophotographic image forming apparatus, comprising the electrophotographic member according to claim 1.
11. An electrophotographic image forming apparatus comprising the electrophotographic member according to any one of claims 1 to 9.
Citation Information
Patent Citations
Organic photoreceptor
JP2016126163A
Intermediate transfer body and image forming apparatus having the same
JP2017187558A